ATTITUDE OF INTRODUCENTS TO SOME ENVIRONMENTAL FACTORS AND ASSESSMENT OF THE DEGREE OF THEIR DECORATIVENESS - Tursunboev Khamdam; Sultashova Oralkhan (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The article deals with the attitude of introducers to some environmental factors and the assessment of the degree of their decorativeness. In the process of mastering introducers, the reaction of plants to unfavorable soil and climatic conditions is of great importance.